Peningkatan Kemampuan Berbicara Melalui Metode Bermain Peran Pada Anak Didik Kelompok B Semester I TK Pertiwi 2 Brumbung Kec. Jepon Kab. Blora Tahun Pelajaran 2015/2016 - Imroatin, Siti, Drs. Surtikanti, M.Pd (2015)
Based on the observations made on children Group B TK Pertiwi 2 Brumbung undeveloped child's ability to speak. This study aimed to describe the increase in the ability to talk through methods play a role. This type of research is a classroom action research. 2 Research Design Cycle with each cycle of four stages: planning, implementation, observation and reflection. The subjects were students Group B TK Pertiwi 2 Brumbung. Data collection technique used observation, field notes and documentation. The results showed an increased ability to speak. Research shows that the average child's ability to speak before action is 48.9%. After the action through the method of playing the role of children's speech increased to 70.6% in the first cycle and the second cycle capability speaking children increased to 87.9%. It can be concluded that, through role-play method can improve students' ability to speak in group B TK Pertiwi 2 Brumbung.